2013
DOI: 10.1159/000354736
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Brain Metastases after Trimodality Therapy in Patients with Esophageal or Gastroesophageal Cancer: Implications for Screening and Surveillance

Abstract: Background: It is unclear whether patients undergoing trimodality therapy (TMT) should be screened or surveyed for brain metastases. Methods: We retrospectively analyzed esophageal cancer (EC) patients who underwent TMT between the years 2000 and 2010. All were systematically staged and surveyed but none had screening or surveillance brain imaging. Results: The median follow-up time for 518 patients was 29.3 months (range 1-149.2); all patients had adenocarcinoma of the esophagus. Of 188 (36.3%) patients who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
1
25
1
Order By: Relevance
“…In their study, they included 403 patients with esophageal cancer who received only Clinical characteristic Japan [19] United States [20] China [18] n = 36 n = 27 n = 31 [23] , 518 esophageal adenocarcinoma patients receiving trimodal therapy were retrospectively analyzed. In that study, distant metastasis was found in 188 cases (36.3%), including 20 cases of BM (3.9%).…”
Section: Auxiliary Treatment Of Esophageal Cancer Promotes Bmecmentioning
confidence: 99%
See 4 more Smart Citations
“…In their study, they included 403 patients with esophageal cancer who received only Clinical characteristic Japan [19] United States [20] China [18] n = 36 n = 27 n = 31 [23] , 518 esophageal adenocarcinoma patients receiving trimodal therapy were retrospectively analyzed. In that study, distant metastasis was found in 188 cases (36.3%), including 20 cases of BM (3.9%).…”
Section: Auxiliary Treatment Of Esophageal Cancer Promotes Bmecmentioning
confidence: 99%
“…BM typically occurs after treatment [4,6,7,18,[20][21][22][23] , although concurrent BM and EC have been rarely reported (less than 10 cases in the literature). In some individual case reports [7,[24][25][26] , especially in misdiagnosed cases [7,25,26] , BM was found before the primary lesion of the esophagus was detected.…”
Section: Misdiagnosis Of Bmec That Occurs Earlier Than the Diagnosis mentioning
confidence: 99%
See 3 more Smart Citations